Assessment of post-menopausal osteoporosis development risk: role of polymorphisms RS1800012, RS1107946 of a gene of COL1A1 and RS731236 and RS11568820 of a gene of VDR - Zyablicev, D. S.; Larin, A. S. (Journal of Education, Health and Sport, 2015)
Zyablicev D. S., Larin A. S. Оцінка ризику розвитку постменопаузного остеопорозу: роль поліморфізмів rs1800012 і rs1107946 гена COL1A1 та rs731236 і rs11568820 гена VDR = Assessment of post-menopausal osteoporosis development risk: role of polymorphisms rs1800012, rs1107946 of a gene of COL1A1 and rs731236 and rs11568820 of a gene of VDR. Journal of Education, Health and Sport. 2015;5(2):333-340. ISSN 2391-8306. DOI 10.5281/zenodo.18861 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A333-340 https://pbn.nauka.gov.pl/works/569107 http://dx.doi.org/10.5281/zenodo.18861 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. УДК 618.173:616.8+616.4]+616.71-008.64:575 Оцінка ризику розвитку постменопаузного остеопорозу: роль поліморфізмів rs1800012 і rs1107946 гена COL1A1 та rs731236 і rs11568820 гена VDR Assessment of post-menopausal osteoporosis development risk: role of polymorphisms rs1800012, rs1107946 of a gene of COL1A1 and rs731236 and rs11568820 of a gene of VDR Д. С. Зябліцев, О. С. Ларін D. S. Zyablicev, A. S. Larin Український науково-практичний центр ендокринної хірургії, трансплантації ендокринних органів і тканин МОЗ України, м. Київ, Україна Ministry of Healthcare of Ukraine Ukrainian science-practical centre of endocrine surgery, transplantation of endocrine organs and tissues Kyiv, Ukraine Abstract Aim: to define the risk of the development of postmenopausal osteoporosis (PO) in dependence of polymorphisms rs731236 and rs11568820 of VDR gene and rs1800012 and rs1107946 of COL1A1 gene. Single nucleotide polymorphisms have defined by means of polymerase chain reaction with electroforetic detection. As a result of research the following conclusion were drawn: major homozygote CC of polymorphism rs 731236 of VDR gene had a protective influence (OR=0,18) concerning development of PO whereas minor genotype TT of this one considerably increased the risk of PO (OR=5,42); major homozygous genotype AA of polymorphism rs11568820 of VDR gene had decreased (OR=0,19), and minor homozygous genotype GG had increased (OR=8,00) the risk of development of PO. The risk of development of PO in the presence of major genotype GG of polymorphism rs1800012 of COL1A1 gene had decreased (OR=0,19), and presence of homozygote TT in this genotype had increased the risk of development of PO (OR=4,50); major homozygote GG of polymorphism rs1107946 of COL1A1 gene had promoted decrease (OR=0,15) the risk of development of PO; minor homozygote TT of this polymorphism, as well as in the previous cases, had increased (OR=3,34) risk of development of PO. Thus, presence at the studied polymorphisms of minor alleles (especially in homozygous option) significantly increased risk of development of PO. Key words: postmenopausal osteoporosis, gene VDR, gene COL1A1, rs1800012, rs1107946, rs731236, rs11568820. Резюме Оценка риска развития постменопаузального остеопороза: роль полиморфизмов rs1800012 и rs1107946 гена COL1A1 и rs731236 и rs11568820 гена VDR. Цель работы – определение риска развития постменопаузального остеопороза (ПО) в зависимости от полиморфизмов rs731236 и rs11568820 гена VDR и rs1800012 и rs1107946 гена COL1A1. Однонуклеотидные полиморфизмы определяли с помощью полимеразной цепной реакции с электрофоретической детекцией. В результате исследования были сделаны следующие выводы: мажорная гомозигота СС полиморфизма rs731236 гена VDR имела протэктивное влияние (OR=0,18) в отношении развития ПО, тога как минорный генотип ТТ этого полиморфизма значительно увеличивал риск ПО (OR=5,42); мажорный гомозиготный генотип АА полиморфизма rs11568820 гена VDR снижал (OR=0,19), а минорный гомозиготный генотип GG повышал (OR=8,00) риск развития ПО. Риск развития ПО при наличие мажорного генотипа GG полиморфизма rs1800012 гена COL1A1 снижался (OR=0,19), а наличие гомозиготы ТТ в этом генотипе увеличивала риск развития ПО (OR=4,50); мажорная гомозигота GG полиморфизма rs1107946 гена Col1A1 способствовала снижению (OR=0,15) риска развития ПО; а минорная гомозигота ТТ этого полиморфизма, как и в предыдущих случаях, увеличивала (OR=3,34) риск развития ПО. Таким образом, присутствие в изученных полиморфизмах минорных аллелей (особенно в гомозиготном варианте) существенно увеличивало риск развития ПО. Ключевые слова: постменопаузальный остеопороз, ген VDR, ген COL1A1, rs1800012, rs1107946, rs731236, rs11568820.